Model of pathogen transmission between livestock and white-tailed deer in fragmented agricultural and forest landscapes. (June 2016) - Guber, Andrey K.; Williams, David M.; Dechen Quinn, Amy C.; Tamrakar, Sushil B.; Porter, William F.; Rose, Joan B.
Abstract: The study summarizes the current knowledge on infection and recovery of white-tailed deer and cattle, and integrates this knowledge into the Soil and Water Assessment Tool (SWAT) via a new add-on module SIR (Susceptible - Infected - Recovered) for predicting pathogen transmission between livestock and deer. New processes modeled by the SWAT-SIR model include: (a) seasonal changes in deer population and habitat; (b) resource selection and seasonal changes in foliage consumption by deer; (c) ingestion of pathogens with water, foliage and via grooming soiled hide by deer and grazing cattle; (d) infection and recovery of deer and co-grazing cattle; (e) pathogen shedding by infected animals; (f) survival of pathogens in manure; (g) kinetic release of pathogens from applied manure and fecal material. The model output is linked with ARC-GIS to allow spatial and temporal analysis of pathogen distribution across the watershed for specific land use, weather and management scenarios. Highlights: We developed an add-on module for SWAT model to predict pathogen transport. The module simulated pathogen transmission between livestock and white-tailed deer. The transmission occurs via pathogen ingestion with water, foliage and grooming. The model output allows spatial and temporal analysis of pathogen distributions.